The Quality Improvement On Integral Mathematics Learning By Guided Discovery Model At Class Xii Building Technique State 2 Vocational High School Salatiga Academic Year 2011/2012 - PRIHANTOMO, HARIS (2012)
Research goals to increase student interest in mathematics learning process integral to the model of guided discovery. Identification of the problems shown in this study is the low math scores cause for students interested in teaching methods and student learning can make a relatively low completeness. The problems identification which is shown on this research is the low of mathematics score cause by uninterested learning method for students and it can make the completeness of students learning relatively low. It is classroom action research, which is done by State 2 Building Technique Class XII at Vocational High School of Salatiga. With these data analysis, it can be found the average score of before the action is 64.00, and the average score of the first cycle is 77.33, on the second cycle is 78.37 and on the third cycle is 83.87. So, from the three cycles above, it can be summarized that there is an increasing score on each cycle which shows the improving achievement on the learning process. The use of guided discovery learning model can increase student interest in learning math competency integral, this is evidenced by the increased interest, motivation, and participation of students in mathematics learning integral. The use of guided discovery learning model can also improve learning outcomes in integral mathematics. The increasing of student learning outcomes can be seen with the learning outcomes that can reach the the Minimum Criteria of Completeness (KKM) with a value of 72 percent and more than 85%.